184. Inducible Clindamycin Resistance Testing on Pediatric Streptococcus pneumoniae Isolates. (4th December 2021) - Olarte, Liset; Swanson, Douglas S; Tabakh, Jennifer E; Banerjee, Dithi; Selvarangan, Rangaraj
Abstract: Background: In 2013, the Clinical and Laboratory Standards Institute recommended inducible clindamycin resistance (ICR) testing on macrolide-resistant Streptococcus pneumoniae isolates, which arises due to the erm B gene. Ribosomal methylation by erm B confers resistance to macrolides (high-level resistance), lincosamides and streptogramin B. The goal of our study is to characterize the prevalence of ICR among pediatric pneumococcal isolates. Methods: We identified erythromycin-resistant(R) (minimum inhibitory concentration [MIC] ≥ 1 µg/mL) and clindamycin-susceptible(S) (MIC ≤ 0.25 µg/mL) pneumococcal isolates from pediatric patients seen at Children's Mercy Hospital from 2007 to 2017. Determination of ICR was achieved via disk approximation (D-zone test) with standard erythromycin (15 µg) and clindamycin (2 µg) disks. Isolates with high-level erythromycin resistance (MIC ≥ 32µg/mL) were also tested for erm B gene by PCR. Positive and negative controls were used for D-zone test and erm B PCR. Results: We identified 289 erythromycin-R pneumococcal isolates; of those 194 (67.1%) were clindamycin-S (Figure 1 ). One-hundred and sixty-nine isolates were available for ICR testing, 166 (98%) isolates represented non-invasive disease samples. Median age of patients with erythromycin-R and clindamycin-S isolates was 19 (range 0.1 – 180) months. None of the isolates expressed ICR based on the D-zone test. Thirteen of those isolates (7.7%) expressed high-level erythromycin-R (MIC range 32-128 µg/mL); all were negative for erm B. The most common serotypes/serogroups among erythromycin-R and clindamycin-S isolates were: 15 (n=22), 35B (n=19), 11 (n=16), 6 (n=16), 19A (n=14) and 33 (n=12). Conclusion: Erythromycin-R and clindamycin-S pneumococcal isolates did not express ICR and isolates with high-level erythromycin-R did not carry erm B. Multicenter studies are needed to determine if ICR testing is required for macrolide-resistant pneumococcal isolates in the PCV13 era. Disclosures: Liset Olarte, MD, MSc, GSK (Research Grant or Support)Merck (Research Grant or Support)Pfizer (Research Grant or Support)Sanofi (Research Grant or Support) Douglas S. Swanson, MD, Merck (Research Grant or Support)Pfizer (Research Grant or Support)Sanofi (Research Grant or Support)